Reaction mechanism and kinetics for carbon dioxide reduction on iron–nickel Bi-atom catalysts. Issue 25 (20th June 2022) - Li, Fuhua; Wen, Huaqiang; Tang, Qing
Abstract : The electrocatalytic reaction mechanism and kinetics of CO2 reduction at the Ni–Fe dual-site were determined based on the grand canonical potential kinetics (GCP-K) method, and a new CO-passivating mechanism was revealed. Abstract : The electrochemical CO2 reduction reaction (CO2 RR) is being accepted as one of the most promising strategies to convert carbon emissions to valuable chemicals and fuels. Among the various types of electrocatalysts, dual-site catalysts have emerged as a new frontier. In particular, the Ni–Fe bi-site not only plays a key role in the biological utilization of CO2 in enzymes but also shows exceptional activity and selectivity for CO evolution in the heterogeneous CO2 RR. However, an in-depth understanding of the reaction mechanism has not been achieved. In this work, we applied the recently developed grand canonical potential kinetics (GCP-K) method to determine the reaction mechanism and kinetics of the CO2 RR on Fe&Ni@g-N6 . Unlike the traditional CO2 RR mechanism on transition metals or single-atom catalysts, the Fe–Ni dual site is firstly passivated by strongly adsorbed *CO, and the real active site of the CO2 RR cycle is at the exposed single Fe site. The predicted overall kinetics has a U onset (10 mA cm −2 ) of −0.99 V to generate CO, and the maximum turnover frequency reaches 961 h −1 per site at U = −1.18 V. The competitive hydrogen evolution reaction (HER) has a greater negative onset potential and does not interfere with the CO2 RR. These predictions show a reasonable agreement with the experiment. The promising performance is correlated with the down-shift and localization of the 3d electronic states of Fe atoms. Our analysis provides a defined mechanism and offers useful insight into designing efficient dual-active-site electrocatalysts.